Larp & Narrative - Hansen, Michael (My University, 2016)
Live action role-playing (larp) is a form of narrative play that engages participants in fictional words within the dialectic of experience (unorganized time) and narrative (organized time). In this thesis I explore the complexities of the fictional worlds created by larps and how the participation in larps constructs requires a different engagement with traditional thoughts about narrative. Discussing fictional worlds theory, Aristotle, Frye, and Ricoeur along side concepts from game studies, such as the magic circle and the frames of exogeny, endogeny, and diegesis, I propose an alternative approach to understanding narrative within larps that looks at the larp worlds and plot as being driven by a process of affirming the identities constructed to participate within the fictional worlds through the mimetic process.
Keywords: live action roleplaying; larp; narrative; play